Mini-fasting Tests Diagnosing Endogenous Hyperinsulinism: a Follow-up of 26 Cases - Felício, J. S.; Koury, C. C.; Martins, C. L. L. P.; Miléo, K. B.; Neto, J. F. A.; de Melo, F. T. C.; de Souza, A. C. C. B. (Experimental and Clinical Endocrinology & Diabetes, 2014)
The supervised 72-h fast remains the gold standard test for the diagnosis of endogenous hyperinsulinism and has recently been suggested to be shortened or even avoided.This study aimed to evaluate whether measurement of blood glucose, insulin and C-peptide levels after a 12 h overnight fast (mini-fasting test), in at least 3 consecutive days, could allow making or ruling out diagnosis of endogenous hyperinsulinism, according to the Endocrine Society’s recent guidelines.We performed 12 h mini-fasting test in at least 3 consecutive days, dosing blood glucose, insulin and C-peptide levels in 26 inpatient patients with pathologically proven endogenous hyperinsulinism.In our series, 100% of patients showed insulin levels of at least 3 μU/ml and C-peptide levels of at least 0.6 ng/ml concomitant with symptomatic hypoglycemia (≤55 mg/dl).It leads to the conclusion that mini-fasting test might avoid, in most cases, prolonged fasting test for the diagnosis of hypoglycemia due to endogenous hyperinsulinism.
Keywords: endocrine pancreas; hypoglycemia; insulinoma